A de novo paradigm for male infertility - Oud, M. S. (2022)
Funding Information: (DFG, CRU326) to C.F. and F.T. This project was also supported in part by funding from the Australian National Health and Medical Research Council (APP1120356) to M.K.O.B., by grants from the National Institutes of Health of the United States of America (R01HD078641 to D.F.C. and K.I.A., P50HD096723 to D.F.C.) and from the Biotechnology and Biological Sciences Research Council (BB/S008039/1) to D.J.E. Funding Information: We are grateful for the participation of all patients and their parents in this study. We thank Laurens van de Wiel (Radboudumc), Sebastian Judd-Mole (Monash University), Arron Scott and Bryan Hepworth (Newcastle University) for technical support, and Margot J Wyrwoll (University of Münster) for help with handling MERGE samples and data. This project was funded by The Netherlands Organization for Scientific Research (918-15-667) to J.A.V. as well as an Investigator Award in Science from the Wellcome Trust (209451) to J.A.V. a grant from the Catherine van Tussenbroek Foundation to M.S.O. a grant from MERCK to R.S. a UUKi Rutherford Fund Fellowship awarded to B.J.H. and the German Research Foundation Clinical Research Unit “Male Germ Cells” Publisher Copyright: © 2022, The Author(s).